Ecological Restoration of Abies religiosa Forests Using Nurse Plants and Assisted Migration in the Monarch Butterfly Biosphere Reserve, Mexico - Carbajal-Navarro, Aglaen; Navarro-Miranda, Esmeralda; Blanco-García, Arnulfo; Cruzado-Vargas, Ana Laura; Gómez-Pineda, Erika; Zamora-Sánchez, Cecilia; Pineda-García, Fernando; O'Neill, Greg; Gómez-Romero, Mariela; Lindig-Cisneros, Roberto; Johnsen, Kurt H.; Lobit, Philippe; et al. (Frontiers in Ecology and Evolution, 2019)
Increasing disturbance events (forest fires, windstorms, pest outbreaks) associated with climate change are creating new ecological restoration challenges. Here, we examine the utility of assisted migration in combination with naturally established nurse plants in order to improve the success of afforestation with Abies religiosa (sacred fir), the overwintering host of the Monarch butterfly (Danaus plexippus). We established high-elevation assisted migration A. religiosa provenance field tests at two sites (Las Palomas and Los Ailes) in the core overwintering areas of the Monarch Butterfly Biosphere Reserve (MBBR), central Mexico. At each site, 2-year-old seedlings were planted either in the open or under existing nurse plants. Three and a half years after planting at the Las Palomas site (5.5 years from germination), A. religiosa seedling survival was 72% under the shade of nurse plants but only 18% in open areas (without shade). At the Los Ailes site, 1 year and a half after planting in the field (3.5 years from germination), survival was 94% and 10%, respectively. There were not significant differences in seedling height increment among populations at either site. The results of our study and those published elsewhere suggest that A. religiosa benefits from shade protection of nurse plants and that population transfer 400 m upward in elevation (i.e., assisted migration) to compensate for future warmer climates does not appear to have any negative impacts on the seedlings, while potentially conferring closer alignment to future climates. If absent in planting sites, we recommend growing nurse shrub species (such as Baccharis conferta) alongside tree seedlings in forest nurseries so that these shrubs can be transplanted to the reforestation site 2 years before planting the tree seedlings.